Click chemistry and drug delivery: A bird's-eye view - Shameer M. Kondengadan; Shubham Bansal; Ce Yang; Dongning Liu; Zach Fultz; Binghe Wang (Elsevier, 2023)
Click chemistry has been proven to be very useful in drug delivery. Due to the availability of a large number of click reactions with a various characteristics, selection of appropriate chemistry for a given application is often not a trivial task. This review is written for pharmaceutical researchers who are interested in click chemistry applications and yet may not be click chemistry experts. For this, the review gives an overview of available click reactions organized by application types. Further, the general understanding of click reactions being fast and high yielding sometimes overshadows the need to analyze reaction kinetics in assessing suitability of a given reaction for certain applications. For this, we highlight the need to analyze the relationship among reaction kinetics, concentration effects, and reaction time scales, knowing that lack of such analysis could easily lead to failures. Further, possible issues such as chemical stability with various click reagents are also discussed to aid experimental designs. Recent examples and extensive references are also provided to aid in-depth understanding of technical details. We hope this review will help those interested in using click chemistry in drug delivery to select the appropriate reactions/reagents and minimize the number of pitfalls.